Comprehensive Bioinformatics Analyses and Experimental Validation of the Cell Cycle Related Protein SAPCD2 as a New Biomarker and Potential Therapeutic Target in Pancreatic Cancer - Liu Y; Li B; Ke L; Luo T; Wu H; Lin J; Deng Y; Huang X; Xu L; Liu Y; Qi J (Journal of Inflammation Research)
Yuting Liu,1,2,* Bo Li,1,2,* Lingling Ke,1,* Tingting Luo,1 Huixian Wu,1 Jiahui Lin,1 Yu Deng,3 Xiuji Huang,4 Liangliang Xu,5 Yuchen Liu,1,2 Jian Qi1 1Digestive Diseases Center, Guangdong Provincial Key Laboratory of Digestive Cancer Research, The Seventh Affiliated Hospital, Sun Yat-Sen University, Shenzhen, Guangdong, 518107, People’s Republic of China; 2Scientific Research Center, Guangdong-Hong Kong-Macau University Joint Laboratory of Digestive Cancer Research, The Seventh Affiliated Hospital, Sun Yat-Sen University, Shenzhen, Guangdong, 518107, People’s Republic of China; 3Laboratory Animal Center, Sun Yat-sen University, Shenzhen, Guangdong, 518107, People’s Republic of China; 4Department of Respiratory and Critical Care Medicine, The Seventh Affiliated Hospital, Sun Yat-sen University, Shenzhen, Guangdong, 518107, People’s Republic of China; 5Department of Ultrasound, Peking University Shenzhen Hospital, Shenzhen Peking University-The Hong Kong University of Science and Technology Medical Center, Shenzhen, 518036, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yuchen Liu, Email liuych83@mail.sysu.edu.cn; Jian Qi, Email qijian@sysush.comPurpose: Pancreatic adenocarcinoma (PAAD) is a highly aggressive cancer with a poor prognosis, reliable markers are urgently needed for early detection and prognosis evaluation. SAPCD2, a cell cycle related gene, has been implicated in tumorigenesis and proposed as a potential therapeutic target in cancer. However, no comprehensive study has explored its expression and regulation, discussed its role in tumor prognosis and immune modulation, along with therapy response in pan-cancer until now.Methods: SAPCD2 expression was analyzed using data from The Cancer Genome Atlas database (TCGA) and Human Protein Atlas (HPA) database. Genetic and epigenetic alterations of SAPCD2 and the immune microenvironment were explored via NCBI, TIMER2 and cBioPortal platforms. Western blot analysis and immunohistochemistry (IHC) were performed to check SAPCD2 protein expression in PAAD cells and tissues. Cell counting kit 8 (CCK8), flow cytometry, and transwell experiments were used to evaluate the role of SAPCD2 in PAAD cell lines.Results: Our study found that SAPCD2 is notably upregulated in various cancers, especially early-stage digestive cancers, and is linked to poor survival in most cancers like PAAD and LIHC. Gene amplification and promoter DNA hypomethylation appear to drive this upregulation. Additionally, SAPCD2 expression correlates with tumor mutation burden, microsatellite instability, and immune scores across several cancers. In PAAD, elevated SAPCD2 levels correlated with reduced immune activity, whereas in stomach cancer (STAD), its prognostic impact appeared immune-independent. In PDAC cell lines, SAPCD2 knockdown reduced proliferation and invasion, and caused reduction of G0/G1 phase. PAAD cells with high SAPCD2 expression showed increased sensitivity to DNA-PK, p38α MAPK, and Bcl-2 inhibitors.Conclusion: SAPCD2 serves as both a prognostic marker and a potential therapeutic target in PAAD, where its low expression may enhance responsiveness to specific drugs. These findings underscore SAPCD2’s dual role in cancer progression and therapy.Keywords: SAPCD2, pan-cancer analysis, pancreatic cancer, biomarker, prognosis